Identifying Low-Risk Patients with Cirrhosis and Acute Gastrointestinal Bleeding That May Not Require Urgent Endoscopy - Zhang S.; Sun M.; Yuan S.; Lin S.; Romeiro F. G.; He Y.; Zhu Q.; Ma D.; Li Y.; Philips C. A.; et al. (My University, 2025)
Introduction: Urgent endoscopy should be performed in patients with cirrhosis and acute gastrointestinal bleeding (AGIB), but this approach is resource-intensive and associated with procedural risks. Therefore, its necessity has been questioned in low-risk patients. This study aims to identify low-risk patients with cirrhosis and AGIB for whom endoscopy may be unnecessary during hospitalization. Methods: Patients with cirrhosis and AGIB who presented with melena alone were retrospectively screened from an international multicenter cohort. They were further classified according to the use of endoscopy. Logistic regression analyses were performed to explore the relationship of Child–Pugh score and hepatocellular carcinoma (HCC) with in-hospital death. Results: Overall, 673 patients were included, of whom 202 (30.0%) did not undergo endoscopy. Child–Pugh score and HCC were significantly associated with in-hospital mortality. There was no death during hospitalization among the 304 patients with Child–Pugh score ≤ 7 and without HCC, who were stratified as a low-risk population. Among them, neither in-hospital mortality (0.0% vs. 0.0%) nor rate of 5-day failure to control bleeding (1.3% vs. 4.7%, P = 0.110) was significantly different between patients who underwent endoscopy and those who did not. Conclusions: Patients with cirrhosis and AGIB, who present with melena alone, and have Child–Pugh score ≤ 7, but without HCC, may not require urgent endoscopy. Trial Registration: This study is a secondary analysis based on the data from our previously registered study (ClinicalTrials.gov identifier NCT04662918).
Keywords: Eczacılık; Temel Eczacılık Bilimleri; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Basic Pharmaceutics Sciences; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (Life); Farmakoloji ve Toksikoloji; Farmakoloji ve Eczacılık; Life Sciences (Life); Pharmacology & Toxicology; Pharmacology & Pharmacy; Farmakoloji (tıbbi); Pharmacology (medical); Acute gastrointestinal bleeding; Cirrhosis; Death; Endoscopy; Risk stratification